Review and taxonomies of assembly and disassembly path planning problems and approaches. (October 2015) - Ghandi, Somayé; Masehian, Ellips
Abstract: Assembly Planning (AP) is one of the most important elements of process planning in manufacturing industries, and is defined as the process of creating a detailed assembly plan to craft a whole product from separate parts considering the final product geometry, available resources, fixture design, feeder and tool descriptions, etc. AP has three main subproblems: (1) Assembly Sequence Planning (ASP), in which a sequence of collision-free operations is computed for bringing assembly parts together, (2) Assembly Line Balancing (ALB), in which some groups of subassemblies are formed and assigned to assembly stations in a way that their workloads are balanced, and (3) Assembly Path Planning (APP), in which collision-free paths for adding parts to a subassembly are computed. Each of the above subproblems has a disassembly version, creating DASP, DALB, and DAPP problems. All of the above problems have proven to be either NP-hard or NP-Complete, and many researches have been conducted to solve them efficiently. While some surveys and reviews exist on the ASP/DASP and ALB/DALB problems, no comprehensive survey exists for APP/DAPP problems, despite their important role in the design process of products as invaluable tools for deploying concurrent engineering, end-of-life processing, maintenance and repair, and decreasing the cost and time of manufacturing products. This paper investigates the relations between the above six subproblems and reviews the state-of-the-art of the APP and DAPP problems and their solution approaches. Through two new taxonomies the properties and categories of APP/DAPP problems and solution approaches are identified and described, the characteristics and applications of the reviewed 60 most relevant works are exposed and analyzed comprehensively, and open problems in the field are identified. Highlights: State-of-the-art review of the Assembly/Disassembly Path Planning (APP/DAPP) field. New taxonomies for categorizing APP/DAPP problem types and solution methods. Critical discussions on research trends, applications and open problems in APP/DAPP.